Metachronous Anal Canal and Prostate Cancers with Simultaneous Definitive Therapy: A Case Report and Review of the Literature - Edward F. Miles; Laura L. Jacimore; John W. Nelson (Case Reports in Oncological Medicine)
Anal canal cancer is rare, accounting for only 1.3% of all gastrointestinal tract malignancies. Prostate cancer incidence is much higher and accounts for 27.6% of all malignancies in men. Treatment guidelines for anal cancer involve radiotherapy to the primary site and draining lymphatics while treatment for prostate cancer can also include pelvic radiotherapy. The literature is silent on the optimum course of action when these two malignancies are found synchronously or metachronously. Herein, we report a case of a patient diagnosed with intermediate risk prostate cancer who, prior to definitive therapy for this first malignancy, was also diagnosed with anal canal cancer. We conclude that a simultaneous approach with radiation therapy and chemotherapy with subsequent boost to the prostate is recommended. Screening for synchronous prostate cancer in male anal canal cancer patients is probably indicated and may preclude suboptimal treatment for a second occult primary.